Common Ownership and Auditor Sharing - Kim, Young Hoon (Contemporary Accounting Research, 2026)
ABSTRACT This study examines whether common ownership by institutional investors is associated with auditor sharing among their investee companies. Auditor sharing can enhance audit quality through facilitated monitoring and improve financial reporting comparability—two benefits that enable common owners to internalize externalities across their portfolio firms (i.e., to reduce negative spillovers from audit failures and to capture positive spillovers from improved comparability across commonly owned peer investees). Using same‐industry company pairs in the United States, I find that common ownership is positively associated with the likelihood of sharing the same audit firm, and this association is stronger when co‐owners have longer investment horizons or more aligned incentives. A quasi‐experimental test leveraging BlackRock's acquisition of Barclays provides consistent evidence. Additional analyses indicate that shared board members serve as a potential channel through which auditor sharing arises. Finally, commonly owned, auditor‐sharing companies exhibit higher audit quality and are more likely to collectively dismiss auditors following revealed failures, consistent with improved oversight. These findings contribute to the literature on shared auditors, auditor choice, and common ownership by showing how a noncontractual relationship induced by common ownership shapes auditor sharing across companies and influences the shared auditor's incentives.